FACTORS RELATED TO PERSONAL HYGIENE IN RESTAURANT WORKERS IN THE BATOH COMMUNITY HEALTH CENTER WORKING AREA, KEC. LUENG BATA, KOTA BANDA ACEH IN 2021 - Devi, Sartika; Zulkifli, Zulkifli; Mawardi, Mawardi; Zakaria, Radhiah; Arbi, Anwar (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2024)
Background: Personal hygiene is an action to maintain a person's cleanliness and health for physical and psychological well-being. Cleanliness and tidiness are very important and necessary so that someone is liked and accepted in society, apart from cleanliness is being necessary therefore  person  can live healthily. Data from the Kota Banda Aceh Health Service in 2019 recorded that out of 542 restaurants, there were 52 (9.59%) restaurants that did not meet the requirements and data  at the Batoh Community Health Center working area recorded that 12.5% did not meet the requirements. Method: This research is descriptive analytical with a cross-sectional design. The population in this study were all  restaurant workers in the Batoh Community Health Center working area, totaling 55 workers. Sampling was carried out using the random sampling technique. Data collection was carried out by interviews from 18 to 22 January 2021. The statistical test used was the chi square test using the SPSS 23 computer program. Results: The results of the study showed that there was a relationship between knowledge (p value=0.011) and length of service (p value=0.003). And there is no relationship between training (p value=0.343) and personal hygiene among restaurant workers. Recommendation: It is recommended that puskesmas officers can increase counselingr and training about personal hygiene for restaurant workers  and the community in the Batoh Puskesmas working area so that they can increase public’s knowledge of the importance of maintaining personal hygiene.